KONSEP LANSIA AKTIF DALAM PERANCANGAN PANTI JOMPO DI KEMANG SELATAN - Haryadi, Sesilia Revalina; Husin, Denny (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2024)
The phenomenon of the number of elderly facilities is still quite insufficient and not proportional to the number of elderly people. The issue of space in nursing homes also still does not meet safety and security standards for the elderly who experience physical limitations. This can cause the elderly to feel uncomfortable and can even experience accidents in living their daily lives. The purpose of this design is to design the needs of the elderly that are intensively met in the design of senior living based on active ageing strategies. Qualitative research methods are carried out by surveys and interviews with individual elderly people or elderly people living in institutions. The steps are carried out by finding data collection surveys and interviews, then determining the needs according to the results of the data that has been found by applying appropriate concepts to existing problems. The design results consist of residential services for independent elderly, non-self-occupancy, elderly care clinic, gardening area as the main program and intergenerational activities as supporting programs such as food court, cooking class, sewing, knitting, music club, book club, and movie club. The project findings are the merging of senior living with intergenerational programs. The novelty of combining the two programs can have a positive impact on both the elderly and the younger generation. Keywords: active; elderly; living; senior living Abstrak Fenomena jumlah fasilitas lansia yang masih cukup kurang dan tidak sebanding dengan jumlah lansia di Indonesia terbilang cukup penting. Isu ruang dalam panti jompo juga belum memenuhi standar keselamatan dan keamanan bagi lansia yang mengalami keterbatasan fisik. Hal tersebut dapat mengakibatkan lansia merasa kurang nyaman bahkan dapat mengalami kecelakaan dalam menjalani kehidupan sehari-hari. Tujuan dari perancangan ini adalah untuk mendesain kebutuhan lansia yang terpenuhi secara intensif dalam rancangan hunian lansia berbasis strategi active ageing. Metode penelitian kualitatif dilakukan dengan survei dan wawancara kepada lansia individu ataupun lansia yang tinggal di panti. Langkah penelitian dimulai dengan mencari data, lalu menentukan kebutuhan sesuai dengan hasil dari data yang sudah ditemukan dengan penerapan konsep yang sesuai untuk permasalahan yang ada. Hasil desain terdiri dari layanan hunian lansia mandiri, hunian non-mandiri, klinik perawatan lansia, area berkebun sebagai program utama dan aktivitas  antargenerasi sebagai program penunjang seperti pujasera, kelas memasak, menjahit, merajut, ruang musik, ruang baca, dan ruang menonton. Temuan proyek adalah penggabungan senior living dengan program antargenerasi. Kebaruan dari penggabungan kedua program dapat memberi dampak positif pada lansia maupun generasi muda.